Bezpośredni wybór sędziów na przykładzie Stanów Zjednoczonych Ameryki - Abu Gholeh, Magdalena; Bury, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
United States is one of the few countries where citizens have a direct influence on the selection of judges. At the level of the state judiciary can be identified five main methods of selecting judges: partisan election, nonpartisan election, merit selection, legislative appointment and gubernatorial appointment. All of them are presented and described in the article. Authors tried to present the american system of appointing judges in a broad perspective. That is why in paper also provide informations about candidates requirements, terms of office, impeachment, recall and retention election. Due to the large diversity of regulations in different states authors included an three attachments which can help to better understand various judicial systems.
Keywords: partie polityczne; sędziowie; wybory; Stany Zjednoczone Ameryki; kadencyjność; wybór merytoryczny; retention election